Improving Bone Health by Optimizing the Anabolic Action of Wnt Inhibitor Multitargeting. (6th May 2021) - Choi, Roy B; Bullock, Whitney A; Hoggatt, April M; Loots, Gabriela G; Genetos, Damian C; Robling, Alexander G
ABSTRACT: Sclerostin antibody (romosozumab) was recently approved for clinical use in the United States to treat osteoporosis. We and others have explored Wnt‐based combination therapy to disproportionately improve the anabolic effects of sclerostin inhibition, including cotreatment with sclerostin antibody (Scl‐mAb) and Dkk1 antibody (Dkk1‐mAb). To determine the optimal ratio of Scl‐mAb and Dkk1‐mAb for producing maximal anabolic action, the proportion of Scl‐mAb and Dkk1‐mAb were systematically varied while holding the total antibody dose constant. A 3:1 mixture of Scl‐mAb to Dkk1‐mAb produced two to three times as much cancellous bone mass as an equivalent dose of Scl‐mAb alone. Further, a 75% reduction in the dose of the 3:1 mixture was equally efficacious to a full dose of Scl‐mAb in the distal femur metaphysis. The Scl‐mAb/Dkk1‐mAb combination approach was highly efficacious in the cancellous bone mass, but the cortical compartment was much more subtly affected. The osteoanabolic effects of Wnt pathway targeting can be made more efficient if multiple antagonists are simultaneously targeted. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC. on behalf of American Society for Bone and Mineral Research.